2021
DOI: 10.20945/2359-3997000000338
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between short and long-term glycemic variability and oxidative stress in type 1 diabetes mellitus under daily life insulin treatment

Abstract: Objectives:The purpose of this study was to investigate the heterogeneity of the association between glycemic variability and oxidative stress markers in T1DM patients under daily life insulin treatment. Subjects and methods: We studied, in a cross-sectional analysis, 76 T1DM patients without clinical chronic diabetes complications and 22 healthy individuals. Were evaluated the shortterm glycemic variability (STGV), long-term glycemic variability (LTGV), oxidative stress markers [8-isoprostaglandin-F2α (Ur-8-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…These studies were, however, conducted in individuals with type 2 diabetes. Studies on the association between short-term GV and oxidative stress in type 1 diabetes have shown heterogeneous results [ 36 ]. Some associations between long-term GV and oxidative stress markers have also been shown [ 37 , 38 ], but most mechanistic studies have focused on short-term GV, and the true factors behind the ability of HbA 1c variability to capture cardiovascular risk are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were, however, conducted in individuals with type 2 diabetes. Studies on the association between short-term GV and oxidative stress in type 1 diabetes have shown heterogeneous results [ 36 ]. Some associations between long-term GV and oxidative stress markers have also been shown [ 37 , 38 ], but most mechanistic studies have focused on short-term GV, and the true factors behind the ability of HbA 1c variability to capture cardiovascular risk are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Given no significant association was observed between albumin and cardiovascular events, the correlation between albumin and LBGI found in our study may only suggest that both albumin and LBGI are indicators of malnutrition status. Moreover, a most recent study found that albuminuria was positively correlated with plasmatic nitric oxide level which is one of the oxidative stress markers positively correlated with the average level of HbA1c [36]. This correlation suggested that albumin might be associated with glycemic variability via oxidative stress pathway.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies showed conflicting results. Cheprasova et al [ 50 ] found a strong positive correlation between glucose concentration and the levels of OS markers and a negative correlation between the activity of antioxidant enzymes and glucose concentration, while Valente et al [ 51 ] reported that the correlations between glycemic variability and OS markers were heterogeneous. The difference in patients’ characteristics or medications might have caused inconsistent results among these studies.…”
Section: Discussionmentioning
confidence: 99%